Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Terbuka Di Kabupaten Pelalawan - Fahanisa, Alya (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2023)
The problem of unemployment is a condition where the fulfillment of the rights to welfare and work has not been fulfilled. Unemployment has always been a problem that needs to be addressed in the economy. In addition, economic conditions that are not always in a normal stable condition are in line with the policies implemented to achieve a better economy. This study aims to see the effect of the Labor Force Participation Rate (X1), Human Development Index (X2), GRDP (X3) and Minimum Wage (X4) on the Open Unemployment Rate (Y) in Pelalawan Regency. This type of research is descriptive research. The data processed is data published by the Central Statistics Agency in the form of Labor Force Participation Rate, Human Development Index, GRDP, and Minimum Wage for 2012-2021. The technique used in this research is multiple linear regression. While the hypothesis test uses the t test to test the variables partially, and the f test to test the variables simultaneously with a significance level below 0.05. From the test results in this study, it is known that partially with the t test that the Labor Force Participation Rate has a negative and insignificant effect, the Human Development Index has a positive and significant effect, GRDP has a positive and insignificant effect. And the Minimum Wage has a positive and significant effect.